Astrocytes mediate neuronal network hyperactivity in early AD. (20th December 2022) - Shah, Disha; Gsell, Willy; Wahis, Jérôme; Luckett, Emma S.; Jamoulle, Tarik; Preman, Pranav; Moechars, Daan; Craessaerts, Katleen; Horré, Katrien; Hendrickx, Véronique; Jaspers, Tom; Wolfs, Leen; et al.
Abstract: Background: Dysfunctions of network activity and functional connectivity (FC) represent early events in Alzheimer's disease (AD), but the underlying mechanisms remain unclear. Astrocytes regulate neuronal activity in the healthy brain, but their involvement in early network hyperactivity in AD is unknown. Method: We analyzed resting‐state functional MRI data from a prospective cohort of patients and from the APP NLF knock‐in mouse model, with the aim to define which regions show early disruptions of functional connectivity (FC) before the presence of amyloid plaques. Next we used in‐vivo two photon calcium imaging to assess activity of astrocytes and neurons. Finally, we modulated calcium activity in astrocytes and assessed the effects on neuronal activity, FC and clinically relevant behavior readouts, i.e. seizure susceptibility and day/night activity. Result: We found that, prior to amyloid accumulation, the human brain shows increased functional connectivity (FC) of the anterior cingulate cortex. Moreover, early increases of cingulate FC showed a positive correlation to amyloid load several years later in the human brain. Interestingly, we found the same FC deficit in the cingulate cortex of the APP NLF knock‐in mouse model, before amyloid deposition. We demonstrate that these FC deficits coincide with decreased calcium activity of astrocytes and increased neuronal activity. Recovery of the early astrocyte calcium deficits resulted in normalization of neuronal hyperactivity, increased FC as well as seizure susceptibility and day/night behavior disruptions. Conclusion: In conclusion, we show for the first time that astrocytes mediate initial features of AD and drive clinically relevant phenotypes.